Efektivitas Metode Demonstrasi Terhadap Keaktifan Belajar Siswa Bab 7 Topik B Kelas IV - Zulfiyatul Jamilah; Nuruddin, Muhammad; Susilo, Claudya Zahrani (IJPSE Indonesian Journal of Primary Science Education, 2024)
Some discrepancies happened are: 1) the teacher is less skilled in implementing the method and concrete learning media, 2) the learning is monotone and unattractive, which causes high boredom, 3) the class management is complex. This research is formulated to discover the learning effectiveness and differences before and after using the demonstration learning method on the student’s learning liveliness in chapter 7 topic B class IV. This research used Pre Experimental Design quantitative learning method with one sample t-test model, and the choosing sample technique was purposive sampling. The data were collected using test instruments, observation, and documentation. The data were analyzed using SPSS 25 version, namely one sample t-test and paired sample t-test, and was presented as a table and narrative to be further concluded. The research results stated that there is learning effectiveness after using demonstration learning method on the student’s learning liveliness with an influence score was 35%.